The Influence Of Company Characteristics And The Quality Of Sustainability Reports On Firm Value (Case Study Of Property Companies Listed On The Stock Exchange In 2021 - 2023) - Hakim, Mauliza Vestya; Kusdiah, Endang; Amah, Mas (Universitas Dehasen Bengkulu, 2025)
The purpose of this research was to identify, for the years 2021–2023, the property sector businesses listed on the Indonesia Stock Exchange and the amount to which internal company variables and sustainability report quality impacted their worth. The internal determinants that were examined include the following: firm size, profitability, leverage, and management's ownership stake in the business. At the same time, ESG (environmental, social, and governance) factors are used to evaluate the sustainability report's quality. A quantitative methodology based on multiple linear regression analysis approaches is used in this investigation. Using saturation sampling methods, data was acquired from fifteen real estate businesses. Aiming to test hypotheses based on the data to be gathered, the research approach is quantitative in character. Data analysis might be done in stages or all at once. The dependent variable on company value (Y) in the multiple linear regression test is firm size (X1), profitability (X2), leverage (X3), and managerial ownership (X4).